Holistic approach in the management of PCOS: a pilot study of an online PCOS-reversal program - Mehta, Manthan N.; Jayaraman, Mahesh; Agarwal, Sharda (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Polycystic ovary syndrome (PCOS) is a complex disorder that can be managed but not permanently cured. Each woman has her own PCOS symptoms and its own root causes. A number of medications are prescribed to women with PCOS. However, a holistic approach could be the best way forward in managing a disease as complex as PCOS. Authors conducted this pilot study called the Sepalika 5-petal PCOS reversal program which consisted of individualized diet plans, magnet acutherapy, fitness regimens, dietary supplements and herbal products to evaluate whether these interventions improve PCOS symptoms, insulin resistance and hyperandrogenism. Methods: A total of 30 patients were recruited online from all parts of India using the PCOS symptom quiz. Various baseline investigations were performed at recruitment. They were suggested personalized diet plans, followed by exercise videos, magnetic acutherapy and herbal and micronutrient supplements. The program spanned over a period of 90 days and patients outlook and quality of life were also assessed at the end of the program. Results: The main goal of most participants was improvement in weight and energy issues, and regularization of periods. Each of these goals were achieved in all participants of the program. Patient-reported outcomes showed a definite improvement in the quality of life of the participants at the end of 90 days. Conclusions: PCOS is a physical - sexual, psychological and social syndrome; therefore, it is necessary to taking a more holistic approach to patient care beyond treating physical symptoms. Larger studies with more objective and subjective endpoints is the way forward.